Reinforcement the Role of the Health Industry of the Army in the Framework of Increasing the Standard of Service and Community Health - Hutajulu, Ruby Wirawan; Fitriati, Rachma (Yayasan Sembilan Pemuda Indonesia, 2023)
The COVID-19 pandemic has become a global health crisis resulting in a large enough need for medicines, vitamins and vaccines, causing people and governments around the world including Indonesia to panic about their availability on the market. Puskesad as the central implementing agency of the TNI-AD according to its main task is to carry out all efforts relating to the development of the health of soldiers, PNS TNI-AD and their families and TNI-AD Units in order to support the duties of the TNI-AD, to carry out these tasks carry out the main function called as health support and health services are also called upon to help solve current health problems. The purpose of this research is to answer how to strengthen the role of the TNI-AD health industry in order to improve the health standard of soldiers and the public. This research method uses a qualitative research design with descriptive analysis. The results of this research are strengthening the role of the TNI-AD health industry through policies, planning and development, strengthening personnel, strengthening budgets, and strengthening marketing. The conclusion from this research is that to achieve this strengthening, a change in organizational form is needed from Satker to BLU with the order of readiness, namely Lafi Puskesad, Labiovak, Laperalatan kesehatan, and Labiomed.